Johnny Boo : twinkle power - Kochalka, James (Kochalka, James. Johnny Boo, 2008)
Johnny Boo has "boo" power and his pet ghost Squiggle has "squiggle" power. But which is better? And might there be a power that is greater than them both? Wiggle power? Giggle power? Squiggle goes on a quest to learn the secret of twinkle power from the twinkling stars, but doesn't have much luck. Instead, a strange and hilarious secret is discovered about Johnny Boo's hair.